Perceptions of fisherfolks towards the establishment of four (4) marine protected areas in the municipality of Tobias Fornier, Antique - Castillo, Keith Andrei V
This study evaluates the perception of fisherfolks towards the establishment of four (4) Marine Protected Areas in the Municipality of Tobias Fornier, Antique. I interviewed a total of 260 fisherfolks in Arobo, Igdanlog, Igdaguit, and Paciencia, and conducted a Focus Group Discussion (FGD) with Fisheries Extension Officer, and Barangay Captains and Barangay Councilor Committee Head on Agriculture and Fisheries of the four barangays. Data from the interviews was complemented by FGD. All the barangays assessed had poor levels of awareness, and there is a significant difference between the level of awareness of fisherfolks from Paciencia and the rest of the barangays with MPA. Most of the fisherfolks are knowledgeable about the purpose of the MPA because the concepts and benefits of implementing MPAs were explained through a series of consultations, meetings, seminars, and trainings. However, most of them are not aware of the ore zone and buffer zone due to the improper demarcation of these zones. Results show that they are aare of the non-permissible activities within MPAs because it clear to them that MPA is a "No Take Zone." But it obscures the other provisions, specifically the permissible activities. Community participation in the management of MPA is an essential factor for the sustainability of the implementation because it brings a sense of "ownership" and accountability among resource users. Strengthening and empowering people's organizations will be a significant step towards securing their participation in management. Find ways to sustainably utilize other ecosystem services provided by the MPA, such as ecotourism and recreation.